A more efficient synthesis and properties of saturated and unsaturated starch esters. (15th September 2022) - Boetje, Laura; Lan, Xiaohong; Silvianti, Fitrilia; van Dijken, Jur; Polhuis, Michael; Loos, Katja
Abstract: This work presents a series of starch esters synthesized via 1, 5, 7-triazabicyclo[4.4.0]-dec-5-ene (TBD) catalyzed transesterifications in dimethyl sulfoxide (DMSO). The reaction was performed with saturated and unsaturated fatty acids (8, 11, and 18 carbon atoms). The degree of substitution (DS) was raised by purging the reaction flask with nitrogen instead of simply performing the reaction under a nitrogen atmosphere. The increase of DS was most obvious for long-chain fatty acids, as an almost complete DS was observed for starch stearate (2.8) and starch oleate (2.7). The products were characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and X-ray diffraction. Starch esters from unsaturated fatty acids have a lower Tg than their saturated analogues. Moreover, contact angle and moisture uptake measurements showed increased hydrophobicity for all starch esters in comparison to pristine starch. Our results show a more efficient method for synthesizing a biobased material that steers into the direction of a material that could replace conventional plastics. Graphical abstract: Unlabelled Image